The influence of available oral collagen supplementation on the function of joints and skin - Dawid Kościołek; Michał Urbaś; Martyna Kępczyk; Aleksandra Kościołek; Kaja Surowiecka; Jakub Misiak; Miłosz Ojdana; Konrad Szalbot; Mikołaj Tokarski; Natalia Marczak (Kazimierz Wielki University, 2024)
Introduction and purpose:     In our work, we focused on presenting the role of collagen supplementation and its impact on skin and joint health. We considered studies discussing the differences in the effects of collagen from various plant and animal sources. We also examined the influence of the degree of hydrolysis on the absorbability of the supplement. The aim of the paper is to comprehensively summarize knowledge on collagen supplementation, differentiating between its sources and forms.   Material and methods:    In our paper, we endeavored to address the subject of oral collagen supplementation comprehensively. We explored studies about various forms and sources of collagen. We also delved into the collagen supplementation impact on skin and joints health and impact of additives in enhancing the positive effect of collagen .   State of knowledge:    Oral collagen supplementation can be beneficial for skin and joints health. It promote collagen synthesis in human body increasing strength of skin and joints. The higher the degree of collagen hydrolysis, the more easily it is absorbed by the body. Additives in the form of vitamin C and A can enhance collagen synthesis.   Results and conclusions:   This review article indicates a growing interest in oral collagen supplementation and its impact on health. Although there are encouraging findings regarding positive effects, further research is necessary to better understand and determine the optimal conditions for achieving maximum supplementation benefits. This information may be crucial for clinical decisions made by physicians regarding joint reinforcement and anti-aging effects on the skin.